2014
DOI: 10.1037/a0038006
|View full text |Cite
|
Sign up to set email alerts
|

What’s easier: Doing what you want, or being told what to do? Cued versus voluntary language and task switching.

Abstract: The current study contrasted cued versus voluntary switching to investigate switching efficiency and possible sharing of control mechanisms across linguistic and non-linguistic domains. Bilinguals switched between naming pictures in Spanish versus English or between reading numbers aloud versus adding their digits, either without or with repetition of stimuli, and with fewer requirements as to when and how much they had to switch relative to previous instantiations of voluntary switching. Without repetition (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
154
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(197 citation statements)
references
References 62 publications
26
154
2
Order By: Relevance
“…Switching costs are assessed by comparing performance on switch trials , when participants are asked to switch into a different language from the one used on the previous trial, to performance on stay trials , when they use the same language as on the previous trial. Consistent with the predictions of the IC model, studies using a variety of paradigms have revealed asymmetrical switching costs in unbalanced bilinguals (e.g., Campbell, 2005; Costa & Santesteban, 2004; Filippi, Karaminis, & Thomas, 2014; Gollan, Kleinman, & Wierenga, 2014; Hernandez & Kohnert, 1999; Jackson, Swainson, Cunnington, & Jackson, 2001; Linck, Schwieter, & Sunderman, 2012; Martin et al, 2013; Meuter & Allport, 1999; Peeters, Runnqvist, Bertrand, & Grainger, 2014; Philipp, Gade, & Koch, 2007; Wang, Kuhl, Chen, & Dong, 2009; Wang, Xue, Chen, Xue, & Dong, 2007) and symmetrical switching costs in balanced bilinguals switching between languages of equal proficiency (e.g., Calabria, Hernandez, Branzi, & Costa, 2011; Costa & Santesteban, 2004; Costa, Santesteban & Ivanova, 2006; Martin et al, 2013), although there have also been exceptions to these findings (e.g., Calabria et al, 2011; Christoffels, Firk, & Schiller, 2007; Costa & Santesteban, 2004; Costa et al, 2006; Declerck, Koch, & Philipp, 2012; Martin et al, 2013; Prior & Gollan, 2011; Tarlowski, Wodniecka, & Marzecova, 2013; Verhoef, Roelofs, & Chwilla, 2009, 2010; Weissberger, Wierenga, Bondi, & Gollan, 2012). …”
Section: Cued Language Switching In Adultssupporting
confidence: 58%
See 2 more Smart Citations
“…Switching costs are assessed by comparing performance on switch trials , when participants are asked to switch into a different language from the one used on the previous trial, to performance on stay trials , when they use the same language as on the previous trial. Consistent with the predictions of the IC model, studies using a variety of paradigms have revealed asymmetrical switching costs in unbalanced bilinguals (e.g., Campbell, 2005; Costa & Santesteban, 2004; Filippi, Karaminis, & Thomas, 2014; Gollan, Kleinman, & Wierenga, 2014; Hernandez & Kohnert, 1999; Jackson, Swainson, Cunnington, & Jackson, 2001; Linck, Schwieter, & Sunderman, 2012; Martin et al, 2013; Meuter & Allport, 1999; Peeters, Runnqvist, Bertrand, & Grainger, 2014; Philipp, Gade, & Koch, 2007; Wang, Kuhl, Chen, & Dong, 2009; Wang, Xue, Chen, Xue, & Dong, 2007) and symmetrical switching costs in balanced bilinguals switching between languages of equal proficiency (e.g., Calabria, Hernandez, Branzi, & Costa, 2011; Costa & Santesteban, 2004; Costa, Santesteban & Ivanova, 2006; Martin et al, 2013), although there have also been exceptions to these findings (e.g., Calabria et al, 2011; Christoffels, Firk, & Schiller, 2007; Costa & Santesteban, 2004; Costa et al, 2006; Declerck, Koch, & Philipp, 2012; Martin et al, 2013; Prior & Gollan, 2011; Tarlowski, Wodniecka, & Marzecova, 2013; Verhoef, Roelofs, & Chwilla, 2009, 2010; Weissberger, Wierenga, Bondi, & Gollan, 2012). …”
Section: Cued Language Switching In Adultssupporting
confidence: 58%
“…While examinations of switching costs have yielded inconsistent findings and appear to be influenced by a variety of methodological factors (e.g., Bobb & Wodniecka, 2013; Gollan, et al, 2014; Runnqvist et al, 2014), there are other ways to measure inhibition within the language switching paradigm. In addition to switching costs , which are believed to index trial-to-trial fluctuations in the control needed to select the correct word in the correct language, global mixing costs are believed to index more sustained control processes (e.g., Christoffels et al, 2007; Monsell, 2003; Prior & MacWhinney, 2010; Rubin & Meiran, 2005).…”
Section: Cued Language Switching In Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that, unlike Gollan and Ferreira (2009) and Gollan et al (2014), we familiarized our participants with the pictures' L2 names, and we also stressed the importance of using L2 for "at least some" of the pictures. It is possible that these two aspects of our procedure made the selection of L2 names somewhat more likely despite the lack of explicit instructions to use L2 as often as L1.…”
Section: Switching Voluntarily In a Non-switching Contextmentioning
confidence: 99%
“…These findings suggest minimal sharing between language control and executive control mechanisms (see also Gollan, Kleinman, & Wierenga, 2015; Gollan, Sandoval, & Salmon, 2011; Prior & Gollan, 2013). Indeed, Gollan et al, (2014) suggested that even when similar patterns are found, different underlying cognitive mechanisms might be involved. For example, switching costs are reduced in both domains when switches are voluntary instead of cued.…”
mentioning
confidence: 99%